Adoption of hand hygiene practices among health care providers - Archanalakshmi, P. A.; A., Meriton Stanly; Paul, Christina Mary (International Journal of Research in Medical Sciences, 2017)
Background: Hand hygiene is the most important measure to avoid the transmission of harmful germs and prevent health care-associated infections. Hand washing with plain soap removes loose transient flora even though it does not remove pathogens from the hands of healthcare workers. Proper hand hygiene is cheap, most effective, easiest and foremost method of reducing health care associated infections. This study was carried out to know the present status of hand hygiene practices and the barriers to adherence. The objective of the study was to assess the adoption of appropriate hand hygiene practices among health care providers and to find out the reasons for non-adoption. Methods: A cross sectional study was done to assess the adoption of appropriate hand hygiene among health care providers (Doctors, nurses, lab technicians) in upgraded/ block PHCs of Thiruvallur district... The data was analysed by SPSS-16. Proportion & chi square test was used to assess the statistical significance at 5% α. Results: In PHC’s there were 32 doctors, 61 nurses and 17 lab technicians which constitute to 110 heath care providers. Hand hygiene practices were satisfactory among 40 (36%) Z = 9 and the difference is statistically significant p<0.05. Conclusions: Hand hygiene protocols will reduce the nosocomial infections. Hand hygiene is the most important measure to avoid the transmission of harmful germs.